Dynamic and Functional Approach to Human Memory in the Brain: A Clinical Neuropsychological Perspective - Gounden, Yannick; Hainselin, Mathieu; Cerrotti, Fabien; Quaglino, Véronique (Frontiers in Psychology, 2017)
The way how cognition is conceived and represented in brain functioning will directly impact clinical investigations of people with cognitive difficulties. This is particularly evident in the field of clinical neuropsychology where methodologies and tools are justified on a fundamental level by the theoretical foundations adopted. The present article outlined how the dominant influence of structural and anatomo-clinical theories of memory have led to a particular conception of clinical investigations. We propose to reconsider these dominant methods in favour of a more dynamic and functional representation of memory that would be clinically more appropriate. More precisely, we argued that relying exclusively on a particular memory conception (i.e. structural) may not be sufficient considering the range of real-life variables affecting a patient’s memory. By extracting clinically meaningful information in more functional and dynamic memory conceptions, we also aim at underlining the potentials advantages of such theories in facilitating personalized assessments and follow up of patients in clinical neuropsychology. We suggest that a dynamic, functional and integrative conceptions of memory would be more coherent with the trend in clinical neuropsychology to promote a more collaborative interaction between the clinician and the patient. Finally, considering the absence of empirical studies on the possible benefits of implementing such recent memory concepts in clinical practice, we encourage researchers and clinicians to test in the field of clinical neuropsychology, the usefulness and explanatory power of more dynamic and functional representation of memory in order to objectively demonstrate its validity outside the research loop.